Biliary Atresia: A Report from the King Abdulaziz University Hospital in Jeddah, Kingdom of Saudi Arabia - Jamal S. Kamal, (Journal of King Abdulaziz University: Medical Sciences, 2023)
Biliary atresia is under misconception notions or the rarity of the problem is unknown in Saudi Arabia. An experience at King Abdulaziz University Hospital, Jeddah, Saudi Arabia, reported in the management of biliary atresia. A retrospective study of cholestasis, surgically explored between January 1997 and December 2010. The data collected included age at presentation and operation, sex, diagnostic methodology, operative procedures, histopathology reports and post-operative results. Twenty-seven cases of biliary atresia; 17 males and 10 females; mean age at presentation was 62 days; mean age for surgical exploration was 75 days. Twenty-four cases of Type A variety; and three of Type B. Last follow-up, 16 (59.25%) live patients; 2 developed esophageal varices; 3 underwent liver transplants; 6 recur jaundice and liver functions deteriorate after initial improvement among the longest survivors. 2 patients with esophageal varieces; 1 patient underwent a liver transplant. 11 (40.7%) deaths caused mainly by severe cholangitis in the early post-operative period and liver failure afterwards. Concluding, state of liver is important for a successful procedure and esophageal varieces has no relation with the length of survival. Biliary atresia is not rare and the lack of publications is due to a delay in the diagnosis and insufficient reporting.